Clinical Efficacy of Platelet-Rich Plasma in the Treatment of Neurotrophic Corneal Ulcer. (20th June 2018) - Wróbel-Dudzińska, Dominika; Alio, Jorge; Rodriguez, Alejandra; Suchodoła-Ratajewicz, Ewa; Kosior-Jarecka, Ewa; Rymgayłło-Jankowska, Beata; Ćwiklińska-Haszcz, Agnieszka; Żarnowski, Tomasz
Abstract : Purpose . Platelet-rich plasma (PRP) is an autologous blood product without preservatives and rich in proteins and growth factors which make it possible for cells to differentiate, proliferate, and migrate, thus stimulating healing and regeneration of tissues. The aim of this study was to evaluate the efficiency of autologous platelet-rich plasma in the treatment of neurotrophic keratopathy. Methods . The study group consists of 25 patients with nonhealing corneal ulcers due to herpes simplex or herpes zoster infection and facial nerve or trigeminal nerve paralysis as a result of a neurosurgical operation caused by a tumour or stroke. The patients were given autologous platelet-rich plasma drops five times a day and additionally preservative-free artificial tears and a vitamin A ointment at night for maximum 3 months. The following were evaluated: best corrected visual acuity (BCVA), healing of corneal surface, subjective symptoms, and changes in corneal thickness with the use of anterior segment optical coherent tomography (AS-OCT). Results . BCVA before the treatment was 0.10 ± 0.14, and after the treatment it was –0.3 ± 0.27 (p = 0.001 ). Improved visual acuity and less subjective symptoms were observed in all patients. Complete healing of the ulceration was observed in 20 patients (80%). Four patients (16%) experienced considerable improvement of their clinical condition (reduced size and depth of the ulceration and inflammatory state: smaller conjunctival injection and swelling, improved visual acuity, and less subjective symptoms). In one of the patients, an amniotic membrane was transplanted due to the lack of improvement of his local condition. In all patients, the progression of corneal thinning was stopped. An average corneal thickness in its thinnest point was 322.3 ± 125.8 µ m before the treatment, and 404.5 ± 118.7 µ m (p < 0.05 ) after the treatment. None of the patients reported general or local side effects of the treatment. Conclusions . Autologous platelet-rich plasma is a blood-based product which seems efficient in the treatment of neurotrophic keratopathy.